2021
DOI: 10.3390/ma14081858
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized High Clay Content Lateritic Soil Using Cement-FGD Gypsum Mixtures for Road Subbase Applications

Abstract: With a lack of standard lateritic soil for use in road construction, suitable economical and sustainable soil-stabilization techniques are in demand. This study aimed to examine flue gas desulfurization (FGD) gypsum, a by-product of coal power plants, for use in soil–cement stabilization, specifically for ability to strengthen poor high-clay, lateritic soil but with a lower cement content. A series of compaction tests and unconfined compressive strength (UCS) tests were performed in conjunction with scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 56 publications
(64 reference statements)
2
3
0
Order By: Relevance
“…The aggregation of the soil particles forms a rough surface, resulting in a well interlocking condition between soil aggregates. The obtained microstructure results in the current research are consistent with previously researched papers [57,68,76,92,93]. The obtained result of the EDX experiment is illustrated in Figure 11.…”
Section: Microstructural and Chemical Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…The aggregation of the soil particles forms a rough surface, resulting in a well interlocking condition between soil aggregates. The obtained microstructure results in the current research are consistent with previously researched papers [57,68,76,92,93]. The obtained result of the EDX experiment is illustrated in Figure 11.…”
Section: Microstructural and Chemical Characteristicssupporting
confidence: 91%
“…In regard to Figure 3, the soil used in this study is a fine-grained lateritic soil similar to that used by previous studies [34,54,[56][57][58][59][60]. Contrary to the results obtained in this study, the results of research carried out by [32,61] revealed a coarse-grained lateritic soil, as seen in Figure 3.…”
Section: Grain Size Distribution (Gsd)supporting
confidence: 59%
“…This low compressive strength indicates that WFGD gypsum has a very low reactivity at ambient temperature. Nevertheless, the slight strength improvement is related to hydration with C-S-H and ettringite formation in the binder matrix [48,49]. The optimum UCS of the WFGD gypsum is 53% greater than that recorded in the study by Liu et al [50].…”
Section: Effect Of Curing Time Ucsmentioning
confidence: 77%
“…Thus, an increase in strength such as UCS resulting from curing time is attributed to the pozzolanic reaction and cementitious hydration processes [36]. Being activation of chemical reactions in the soil can be perceived through strength development with curing time so that when there is no strength gain with curing time, the chemical reaction is passive [64]. Moreover, the pH of soil increases in the existence of OH − (alkalinity increases), resulting in strong and lasting pozzolanic reaction and cementitious hydration in which the Ca +2 provided by cement enters to chemical reaction with Si an Al of soil.…”
Section: Unconfined Compressive Strength (Ucs) and Durabilitymentioning
confidence: 99%